Match of Negative Stiffness and Viscous Damping in a Passive Damper for Cable Vibration Control - Peng Zhou; Qinghe Fang (Shock and Vibration)
Match of negative stiffness and viscous damping in a passive negative stiffness damper (NSD) is studied for the vibration control of stay cables in this paper. At first, a discrete model of the stay cable with an NSD attached perpendicularly near the support is established. Under sinusoidal excitations, forced responses of the system are derived theoretically, which results in an asymptotic form for the additional modal damping ratios. Then, experimental results are presented to verify the discrete model and the corresponding theoretical derivations. Subsequently, numerical analysis is performed further to show the optimal match of negative stiffness and viscous damping, which is a function of the attachment location. The energy dissipated by the NSD and the cable energy are analyzed, thereby demonstrating the change trend of the additional modal damping ratios. Moreover, the energy distribution along the cable is investigated to reveal the effect of the negative stiffness and viscous damping. This study demonstrates the control mechanism of negative stiffness and viscous damping in the passive damper and is of practical significance for designing the optimal match of the damper parameters for cable vibration control.